2014
DOI: 10.1093/schbul/sbu123
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Fractional Anisotropy in Patients With Childhood-Onset Schizophrenia, Their Healthy Siblings, and Normal Volunteers Through DTI

Abstract: Of those regions, patients with COS, and their healthy siblings had significantly lower mean FA in the left and right cuneus as compared to the healthy volunteers (P < .005). Together, these findings represent the largest DTI study in COS to date, and provide evidence that WM integrity is significantly impaired in COS. Shared deficits in their healthy siblings might result from increased genetic risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 44 publications
3
17
0
Order By: Relevance
“…Siblings carry increased risk for developing schizophrenia (25,38), and therefore, these findings suggest that the FA and KA factors may be potential endophenotypes associated with genetic or familial liability for schizophrenia. The DTI-FA finding replicates previous reports (39,40), but the findings from DKI and PDI in siblings are unique. The processing-speed deficit in the unaffected siblings of the patients is also nearly fully explained by the DTI and DWI factors, again ruling out antipsychotic medication as a primary cause for the finding.…”
Section: Regression Stepsupporting
confidence: 89%
“…Siblings carry increased risk for developing schizophrenia (25,38), and therefore, these findings suggest that the FA and KA factors may be potential endophenotypes associated with genetic or familial liability for schizophrenia. The DTI-FA finding replicates previous reports (39,40), but the findings from DKI and PDI in siblings are unique. The processing-speed deficit in the unaffected siblings of the patients is also nearly fully explained by the DTI and DWI factors, again ruling out antipsychotic medication as a primary cause for the finding.…”
Section: Regression Stepsupporting
confidence: 89%
“…12,29 Whereas the cause of these alterations is still unknown, there is significant evidence for heritability of WM integrity of specific brain regions in subjects with schizophrenia and their unaffected relatives. [16][17][18] These findings suggest that WM integrity measures may be useful endophenotypes for genetic studies of schizophrenia. 13 To date, none of the significant genome-wide genetic variations associated with schizophrenia have been found to explain the differences in WM integrity seen in schizophrenia patients.…”
Section: Discussionmentioning
confidence: 83%
“…15 It is unclear how WM integrity abnormalities relate to the underlying genetic architecture of Schizophrenia, nevertheless the endophenotypic importance of FA for schizophrenia is further supported by recent studies showing that many brain regions showing significant decrease in FA in subjects with schizophrenia (including childhood-onset schizophrenia) were also decreased similarly but with smaller effects in their relatives, with a continuous FA decrease from healthy subjects to relatives to subjects with schizophrenia. 16,17 Thus global WM integrity (as measured by FA) may provide a good biological endophenotype to explain genetic differences in the risk for schizophrenia. 18,19 In this study, we sought to investigate whether oligodendrocyte gene sets associated with schizophrenia are also associated with WM integrity.…”
Section: Introductionmentioning
confidence: 99%
“…Gogtay et al (2012) and Moran et al (2015) found a delayed white matter growth trajectory and decreased FA in adolescent COS siblings, Boos et al (2013) and Hoptman et al (2008), found increased FA in adult first-degree relatives of AOS, while others (Harms et al, 2015;Koivukangas et al, 2015) found no differences in AOS relatives compared to controls.…”
Section: Introductionmentioning
confidence: 94%
“…In addition, COS is a rare and more severe form of AOS and has a more pronounced genetic risk (Asarnow and Asarnow, 1994;Asarnow and Forsyth, 2013;Asarnow et al, 2001;Nicolson and Rapoport, 1999). There have been extremely few DTI studies in this population; Moran et al (2015) and Clark et al (2011) found decreased FA in COS patients, and Ashtari et al (2007) found decreased FA in early onset schizophrenia (defined as onset before the age of 18) patients.…”
Section: Introductionmentioning
confidence: 99%